Accuracy of Spiral Laminar Flow, Spectral Broadening and Murmur / Thrill as Av-Shunt Maturuty Predictors in Dr. Mohammad Hoesin General Hospital Palembang - Sefta Jaka; Kemas Muhammad Dahlan; Jaka Fahmi; Erial Bahar (Sriwijaya Journal of Surgery, 2020)
Background: Hemodialysis is a therapy for end-stage cornic kidney disease (ESRD) which is most often used as renal replacement therapy. Vascular access for hemodialysis is essential in the management of patients with chronic kidney disease. One type of vascular access is av fistula. A well-matured AVF is needed in order to function optimally during the hemodialysis process. The study of Srivastava et al. In India examined a predictor parameter of the maturation of AVF using Doppler ultrasound. The parameters studied were Spiral Laminar Flow (SLF), Spectral Broadening and Murmur / thrill. The results of this study state that SLF is the most important and early predictor of AVF maturation.5 Research on the accuracy of spiral laminar flow, spectral broadening and murmur / thrill as predictors of av-shunt maturity has never been carried out in Indonesia. This encourages this research to be carried out. Methods: This type of research is the prognostic test. The study was conducted in the vascular and endovascular subdivisions from July - September 2020 or until the number of research samples is met. Results: There were 30 samples in this study, Murmur / thrill had high sensitivity and specificity values ​​on day 21 while SLF and spectral broadening had very high sensitivity and specificity values ​​in predicting AVF maturase from day 7th and 21th, also had a significant association with AVF maturase (p < 0.001). Conclusion: Murmur / thrill on 21th day can be a perdictor for maturity of AVF